The Effects of Cosmos caudatus (Ulam Raja) on the Levels of Expression of Nrf2 Target Genes in Mice Liver - Abdullah, Azman; Phern, Tan Chung; Rahim, Nur Fatihah Hanis Mohamad; Zaharuddin, Nur Izzati; Salihin, Nurdayana Maulat; Yusof, Ahmad Hilmi; Jaarin, Kamsiah; Kamisah, Yusof; Saad, Qodriyah Haji Mohd; Fahami, Nur Azlina Mohd; Radman, Harizz Miszard (Journal of Pharmacy and Nutrition Sciences, 2017)
Background: Cosmos caudatus (Ulam Raja) is an appetizer (ulam) eaten with rice in Malaysia. Previous studies showed that Cosmos caudatus possess high antioxidant content. Nrf2 is a transcription factor which regulates the expression of phase II enzymes and antioxidant proteins. The aim of this study is to investigate the effects of Cosmos caudatus aqueous extract (UR) on the expression of Nrf2 target genes in mice liver. Methods: ICR white mice were treated for 21 days with different doses of UR (100, 500, 1000 mg/kg) through oral gavage. Control mice were only given distilled water. After 21 days, the mice were sacrificed and their livers harvested. Total RNA was extracted, reverse transcribed and subjected to qPCR to detect Nrf2 target genes expression. Results: Administration of 100 mg/kg UR significantly increased NQO1 expression in mice liver. Administration of 500 mg/kg UR significantly increased HO-1 liver expression. Administration of 100 and 500 mg/kg UR significantly increased GSTA1 liver expression. Administration of 500 and 1000 mg/kg UR significantly increased GSTM3 liver expression, whereas GSTP and GSTM1 liver expression was significantly decreased at similar doses. Administration of all doses of UR significantly decreased the expression of GSTA3, SOD3 and GCLC in mice liver. Conclusion: UR administration mostly resulted in downregulation of Nrf2 target genes. However, conclusive evidence can only be made through the use of Nrf2 knockout mice or by performing Nrf2 nuclear translocation studies.